Philippine agricultural and food policies: Implications for poverty and income distribution - Cororaton, Caesar B.; Corong, Erwin (International Food Policy Research Institute, 2009)
The Philippines has undergone a series of trade reforms since the mid-1980s that have reduced protection on nonagricultural goods. However, protection on key food items is still in effect, and this has led to high domestic food prices. Such high prices have a considerable negative effect on poverty because more than 60 percent of the consumption of poor Filipino households is for food. The special product arguments of the World Trade Organization increase the pressure to maintain the existing high levels of food protection in the country. Special products treatment provides developing countries with the flexibility to implement tariff reduction programs over an extended period for certain self-designated products. These special product discussions are based on food security, livelihood, and rural development arguments. This research report assesses the poverty and income distribution implications of trade reform that is focused on agriculture and major food items (rice, corn, sugar, beef, chicken, pork, processed meat products, fruits and vegetables, and processed fruits) in the Philippines. A dynamic-recursive computable general equilibrium model calibrated to the social accounting matrix for the Philippine economy for the year 2000 and a microsimulation model that uses the 2000 Family Income and Expenditure Survey are used to analyze possible policy shifts. The simulation results indicate that trade reform in agriculture and major food items will have favorable effects on factor prices and bring about a significant reduction in consumer prices. Real household income will increase while poverty and income inequality decline. These findings therefore imply that maintaining existing trade protections on agricultureand major food items—which drive food prices up—will not solve the problem of poverty and income inequality in the Philippines. In the year 2000 the incidence of poverty in the Philippines was 34 percent. In 2003 it declined to 30.4 percent. The incidence of poverty in rural areas is higher than that in urban areas: 48.8 percent and 18.6 percent in 2000, respectively. Over the past two decades, significant structural changes have taken place in the Philippine economy. The share of agriculture in the total gross domestic product has declined. The country has switched from being a net exporter to a net importer of agricultural products and food items. The widening trade gap in agriculture and food has made the Philippines vulnerable to fluctuations in the world market. For example, the international rice crisis in 2008 has adversely affected the domestic market for rice in the Philippines. The deterioration in the net trade position of the country in food has largely been caused by the high growth in domestic food demand relative to production. Domestic food production lags behind demand because of declining productivity. There is increasing demand for food items with higher income elasticities, and there is also increasing pressure from high population growth. To address this growing trade gap in agriculture and food, the government has adopted a strategy to improve rice productivity. This is a step in the right direction: based on our rice productivity simulation results, higher rice productivity will increase domestic production and reduce imports of rice. Most importantly it will reduce consumer prices. Most of the benefits of improved rice productivity would go to the households in the first decile of the population, since rice has the largest share in their consumption basket relative to the rest of the household groups. There is a reduction in poverty incidence and income inequality. However, implementation of the Philippine government’s rice productivity program is costly, inefficient, and ineffective. In 2001 the government introduced a new technology, hybrid rice. Its adoption was aggressively pursued by the government through the Hybrid Rice Commercialization Program (HRCP). Under the HRCP the production of hybrid rice seeds is supported by the government through (1) procurement of seeds at a guaranteed price, (2) distribution of the procured seeds to participating farmers at half the procurement price, and (3) payment of additional money to participating farmers to help defray their fertilizer input costs. The government has devoted significant resources, through a system of subsidies, to supporting the HRCP. However, the results are not encouraging. The adoption rate of hybrid rice is very low. There is a high dropout rate among participating farmers, because hybrid rice seeds are so expensive and farmers have to purchase them every planting season rather than reusing them (which would result in drastically decreased yields). The massive government subsidies have distorted the ability of farmers to make an informed choice between hybrid and inbred rice varieties. Thus instead of supporting the HRCP the government should spend its limited resources on research and development that focuses on improving the yield of inbred rice. Enhancing an inbred-based system that is adapted to farmers’ familiar practice of saving, reusing, and exchanging seeds would be a more responsive approach to improving productivity than promoting such costly technologies as hybrid rice, which has not yet achieved commercially viable levels.